2012
DOI: 10.1095/biolreprod.112.100008
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelinase Activity in Mother's Milk Is Essential for Juvenile Development: A Case from Lactating Tsetse Flies1

Abstract: Sphingosine is a structural component of sphingolipids. The metabolism of phosphoethanolamine ceramide (sphingomyelin) by sphingomyelinase (SMase), followed by the breakdown of ceramide by ceramidase (CDase) yields sphingosine. Female tsetse fly is viviparous and generates a single progeny within her uterus during each gonotrophic cycle. The mother provides her offspring with nutrients required for development solely via intrauterine lactation. Quantitative PCR showed that acid smase1 (asmase1) increases in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 43 publications
2
48
0
Order By: Relevance
“…For determination of the knockdown phenotypes, flies were injected either 1–2d after adult emergence with siRNAs targeting genes expressed early in pregnancy ( Met , gce and JHAMT ) or 7–9d after adult emergence to target genes expressed late in pregnancy ( bmm and FOXO ). Previous studies have shown that siRNA injection into the mother has no discernible effect on larval transcript levels (Attardo et al, 2012; Benoit et al, 2012). Three to five days after siRNA injection, expression levels of target and downstream genes were determined by qPCR (as described) and normalized to tub after removal of the larva.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…For determination of the knockdown phenotypes, flies were injected either 1–2d after adult emergence with siRNAs targeting genes expressed early in pregnancy ( Met , gce and JHAMT ) or 7–9d after adult emergence to target genes expressed late in pregnancy ( bmm and FOXO ). Previous studies have shown that siRNA injection into the mother has no discernible effect on larval transcript levels (Attardo et al, 2012; Benoit et al, 2012). Three to five days after siRNA injection, expression levels of target and downstream genes were determined by qPCR (as described) and normalized to tub after removal of the larva.…”
Section: Methodsmentioning
confidence: 98%
“…Female flies were mated 3d after emergence and stored in groups of 15 flies. Female flies were collected for analysis according to developmental markers based on the progeny developmental state which were established to analyze pregnancy according to previous studies (Attardo et al, 2006; Benoit et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During each lactation cycle, the milk gland secretes up to 25 mg of milk that consists primarily of lipids and proteins (9). Twelve proteins have been identified as the major constituents of tsetse milk (10)(11)(12)(13). Lipids present in tsetse milk are generated either from metabolized blood meals or via lipolysis of stored fat body lipids (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Furthermore, based on microarray analysis, it was found that SMPD expression levels decreased with the sugar regulation (Zinke et al, 2002). Interestingly, it was suggested that the silence of SMPD gene by siRNA has strong influence on pregnancy and progeny development in Glossina morsitans morsitans Westwood (Diptera: Glossinidade) (Benoit et al, 2012). However, the function of SMPD in bees hasn't been explored.…”
Section: Introductionmentioning
confidence: 99%